Characteristics of Capacitors Based on Ionic Liquids: From Dielectric Polymers to Redox-Active Adsorbed Species. (30th August 2016) - Lust, Enn; Siinor, Liis; Kurig, Heisi; Romann, Tavo; Ivaništšev, Vladislav; Siimenson, Carolin; Thomberg, Thomas; Kruusma, Jaanus; Lust, Karmen; Pikma, Piret; Anderson, Erik; Grozovski, Vitali; et al.
Abstract : Influence of chemical composition of ionic liquids and their mixtures on the electrical double layer characteristics of the cupercapacitors (EDLC) has been studied by cyclic voltammetry, electrochemical impedance spectroscopy, constant current charge-discharge and constant power discharge methods. It has been shown that addition of 1-ethyl-3-methylimidazolium iodide (EMImI), EMImBr or EMImCl to EMImBF4 increases differential capacitance. D-glucose and TiC have been used for preparation of the carbon powders. Additional thermal pyrolysis and/or carbon dioxide activation steps were applied for activation of the electrode materials. The EDLCs based on EMImBF4 + 5 wt% EMImI demonstrated nearly 50% higher stored charge than those with pure EMImBF4 . Noticeable increase in specific capacitance up to 245 F g -1 at 1.0 V, specific energy (36.7 Wh kg -1 ) and specific power (30 kW kg -1 ), and minor increase in characteristic relaxation time constant (from 1.45 s to 1.48 s) has been established for EDLCs containing EMImI.